Some Ring Structures of Skew Genaralized Power Series Rings - Prachi Juyal; Satyajeet Singh; Seema Saini (IndoMS, 2022)
In the current article, we are going to investigate a relationship between some abstract ring structures (weakly PP-rings, clean rings, uniquely clean rings and n-clean rings) along with the skew generalized power series rings A[[N, ϑ]], where A is one of the ring structures described above, (N, ≤) represents a strictly ordered monoid while ϑ : N → End(A) represents a monoid homomorphism. We shall propose unified extensions of the above-mentioned ring structures by employing specific conditions along with their proofs.